2007
DOI: 10.1177/0731684407079423
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Sun Hemp, Banana and Sisal Fiber Reinforced Polyester Composites

Abstract: Experiments are conducted to find out the tensile properties of short sun hemp, banana, and sisal fiber reinforced composites. Length of these natural fibers and fiber weight are varied and are impregnated in polyester resin to prepare tensile test specimen. Optimum values of fiber length and fiber weight ratios are found through experimental results. Analysis is done on these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 6 publications
1
22
0
4
Order By: Relevance
“…Las propiedades de un MC dependen de muchos factores como la resistencia y orientación del material de relleno en el compuesto, los tratamientos superficiales de las fibras, el procedimiento de fabricación del compuesto y el tipo de matriz, entre otros (Udaya Kiran, et al, 2007).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Las propiedades de un MC dependen de muchos factores como la resistencia y orientación del material de relleno en el compuesto, los tratamientos superficiales de las fibras, el procedimiento de fabricación del compuesto y el tipo de matriz, entre otros (Udaya Kiran, et al, 2007).…”
Section: Resultados Y Discusiónunclassified
“…Sin embargo, y a pesar de que en este trabajo fue utilizado el modo de fabricación por moldeo manual, que no permite contenidos de fibra por encima del 14-15% (Dittenber, et al, 2012), se lograron mejoras sensibles en las propiedades mecánicas de los MC respecto de las que se observaron en los especímenes sin tratar. Debido a que el incremento en el porcentaje de fibra mejora la unión con la matriz y facilita la distribución de las cargas de tensión (Udaya Kiran, et al, 2007), sería de esperar que, usando otra técnica de fabricación que permita incrementar el porcentaje de fibra, los MC fabricados con FSP modificadas lograrían desempeños mecánicos superiores. De hecho, en la tabla 1 se puede observar que para las FB (carga del 20%), hay un incremento en la resistencia última a la tracción y del módulo de Young.…”
Section: Prueba De Tensiónunclassified
“…O'Dell (1997) used non-woven jute fibers to prepare UPE panels and found that TS, tensile modulus, and flexural modulus of the jute specimens were half the values of the glass fiber-reinforced UPE composites; IT and TS were also lower. The comparison of sisal, jute, flax, and glass fiber-reinforced UPE composites has been carried out, and the results suggested that among the three natural fibers reinforced composites, the jute-reinforced UPE composites exhibited the best FS and TS, and the worst IT (Rodríguez et al 2005;Udaya Kiran et al 2007). In another investigation, Hill and Abdul Khalil (2000) have used non-woven mats of random coir and oil palm fibers (0 to 55 wt.%) to reinforce UPE using compression moulding, and FS values of all the composites were found to be lower than those for plain UPE at all fiber contents.…”
Section: Introductionmentioning
confidence: 99%
“…Venkateshwaran et al [10] reported that an increase in banana fiber length of up to 15 mm and a 16% weight ratio increases the tensile strength and modulus of a banana/epoxy composite. However, in order to achieve higher mechanical properties, Udaya et al [11] suggested an optimal fiber length and fiber weight ratio of 30 mm and 57%, respectively. However, the optimal findings for fiber treatment and fiber loading are still inconsistent.…”
mentioning
confidence: 99%